Exploring university–firm collaboration in teaching: A case study of co-creation. Issue 5 (October 2022) - de Fátima Cruz, Maria; Franco, Mário; Rodrigues, Margarida
Recently, some authors have pointed out that the subject of university–firm collaboration (UFC) in the teaching context has been neglected. To fill this gap, and considering that educational provision is co-created with various stakeholders, this study aims to provide an exploratory characterization of the current state of UFC in the teaching context and to explore UFC as a mechanism for the co-creation of value. A qualitative approach was chosen, through a case study applied to one faculty at a Portuguese university. Data were obtained through documentary analysis and interviews with people in charge of this faculty. The results suggest that collaboration activities in this domain occur, albeit not systematically or in a planned way. The involvement of the current faculty direction in stimulating this collaboration is recognized, and the leaders see this phenomenon as a mechanism for co-creating value between firms and academia. As a practical contribution, the study proposes a set of recommendations to encourage such UFC. The scientific contribution arises from the presentation of a conceptual structure which explores the UFC phenomenon in the teaching context, bringing together the perspectives of collaboration and the co-creation of educational provision, as well as presenting a number of suggestions for future research.